Facilitative factors in the implementation of the mathematics curriculum in science high schools - Galido, Lourdes Paune (2005)
With the objective of identifying the factors that facilitate the efficient implementation of the mathematics curriculum in science high schools, the study investigated the prevailing conditions and practices in the implementation of the mathematics curriculum in these schools. The results of the study suggest that science high schools must be exclusive schools separate from the regular secondary schools. Administrators are preferably mathematics or science majors with graduate degrees and sufficient number of years of teaching experience. Student admission and retention policies must be stringent. Funds must be allocated for faculty development.
"March 2005."
Thesis (Ph.D. Mathematics Education)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching (Secondary) -- Philippines -- Lanao del Norte; Mathematics -- Study and teaching (Secondary) -- Philippines -- Lanao del Sur; High schools -- Curricula -- Philippines -- Lanao del Sur; High schools -- Curricula -- Philippines -- Lanao del Norte